PENGARUH PROBLEM BASED LEARNING BERBANTUAN MEDIA AUDIO VISUAL TERHADAP KETERAMPILAN BERPIKIR KRITIS SISWA PADA PEMBELAJARAN IPAS KELAS V SD - Juni Harza, Zalfi; Syahrul Rizal, Muhammad; Fitra Surya, Yenni; Hana Pebriana, Putri; Sumianto, Sumianto (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aimed to determine the effect of the Problem Based Learning (PBL) model assisted by audio-visual media on students’ critical thinking skills in IPAS learning for Grade V at SD Negeri 014 Batu Belah. This research employed a quantitative approach using a quasi-experimental design with a Non-Equivalent Control Group Design. The research subjects consisted of an experimental class and a control class. Data were collected through pretest and posttest of critical thinking skills and were analyzed using descriptive statistics and a t-test. The results showed that the average posttest score of the experimental class was higher than that of the control class. The hypothesis testing indicated a significance value of 0.044 < 0.05, therefore the alternative hypothesis was accepted. This finding indicates that the implementation of the Problem Based Learning model assisted by audio-visual media has a significant effect on students’ critical thinking skills. Thus, it can be concluded that the Problem Based Learning model assisted by audio-visual media is effective for IPAS learning as it can increase student engagement and train students’ critical thinking abilities. This model can be used as an alternative learning strategy for elementary school teachers.